2018
DOI: 10.31328/ja.v12i1.546
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-faktor yang mempengaruhi produksi usaha ternak babi di Teluk Doreri Kabupaten Manokwari

Abstract: ABSTRAKStudi ini bertujuan untuk menentukan faktor-faktor yang berpengaruh terhadap produktivitas usaha ternak babi di Teluk Doreri, Manokwari Papua Barat. Data diambil dari 33 peternak babi yang bermukim di sekitar Teluk Doreri, Manokwari. Data yang dikumpulkan berupa data primer, antara lain karakterisktik petani, terdiri dari umur, pendidikan, pengalaman beternak babi, dan data terkait dengan produksi usaha ternak babi, antara lain jumlah dan tipe pakan sumber energi dan protein, jumlah induk yang dimiliki … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…(Djawa, 2022) states that pigs need feed with balanced and perfect nutrition, to obtain optimal reproduction and meat production. The results of this study are following the results of research conducted by (Widayati et al, 2018) nokwari coast generally provide a mixed feed from garden produce, food stall waste, market waste, kitchen waste and tofu paste to pigs, because it is cheaper and easier to obtain than using the commercial feed.…”
Section: Feedsupporting
confidence: 65%
See 1 more Smart Citation
“…(Djawa, 2022) states that pigs need feed with balanced and perfect nutrition, to obtain optimal reproduction and meat production. The results of this study are following the results of research conducted by (Widayati et al, 2018) nokwari coast generally provide a mixed feed from garden produce, food stall waste, market waste, kitchen waste and tofu paste to pigs, because it is cheaper and easier to obtain than using the commercial feed.…”
Section: Feedsupporting
confidence: 65%
“…Workers in the traditional pig rearing system generally use several family members who take turns to help run the business, while the amount of time given is not proportional to the number of workers. If the number of hours worked as a benchmark may be different, such as the results of research obtained by (Widayati et al, 2018), the outpouring of working hours of farmers has a positive effect on the productivity of pig farming in Doreri Bay. Umeh et al (2015) and Zhang et al (2019) also obtained the same result, namely the outpouring of working hours for pig farmers in Nigeria has a positive effect on production and business income.…”
Section: Feedmentioning
confidence: 99%
“…The outcome of this phenomenon revealed that this phenomenon, it reveals that consumers and farmers do not have preference in determining chosen breed to buy and breed to sold [27]. The breeds of swine in WNGP are not varied a such breed in outside WNGP and Indonesia [28,29,30]. In Europe, ASIA, America, breeds can determine the costs, sold, prices and gained income generation [31][32][33][34][35]21].…”
Section: Discussionmentioning
confidence: 99%